2020
DOI: 10.5811/westjem.2020.3.45882
|View full text |Cite
|
Sign up to set email alerts
|

Novice Physician Ultrasound Evaluation of Pediatric Tricuspid Regurgitant Jet Velocity

Abstract: Introduction Pulmonary hypertension, associated with high mortality in pediatric patients, is traditionally screened for by trained professionals by measuring a tricuspid regurgitant jet velocity (TRJV). Our objective was to test the feasibility of novice physician sonographers (NPS) to perform echocardiograms of adequate quality to exclude pathology (defined as TRJV > 2.5 meters per second). Methods We conducted a cross-sectional study of NPS to assess TRJV by echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…During that study novice physician sonographers were graded by the study's primary cardiologist using the same grading rubric as this educational intervention (Document S5). In that study novice sonographers obtained a satisfactory apical 4-chamber view in 85% (95% CI 77.1-92.9), positioned the color box accurately 65% (95% CI 54.5-75.5), optimized TRJV color signal 78.7% (95% CI 69.8-87.7), and optimized continuous-wave Doppler in 55% (95% CI 44.1-66.0) of echocardiograms [13]. Future research into the implementation of this curriculum could compare novice performance to the gold standard of sonographer performed comprehensive echocardiogram to provide further validation of skill acquisition.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…During that study novice physician sonographers were graded by the study's primary cardiologist using the same grading rubric as this educational intervention (Document S5). In that study novice sonographers obtained a satisfactory apical 4-chamber view in 85% (95% CI 77.1-92.9), positioned the color box accurately 65% (95% CI 54.5-75.5), optimized TRJV color signal 78.7% (95% CI 69.8-87.7), and optimized continuous-wave Doppler in 55% (95% CI 44.1-66.0) of echocardiograms [13]. Future research into the implementation of this curriculum could compare novice performance to the gold standard of sonographer performed comprehensive echocardiogram to provide further validation of skill acquisition.…”
Section: Discussionmentioning
confidence: 87%
“…A previously published prospective research study by Binder et al tested sonographer's ability to physically perform TRJV scans (second stage) [13]. During that study novice physician sonographers were graded by the study's primary cardiologist using the same grading rubric as this educational intervention (Document S5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown the utility of estimating the tricuspid regurgitant jet to detect acute right ventricular strain in evaluating patients with pulmonary embolism in the emergency department. [56][57][58][59] The existing literature extensively supports the use of ultrasound in cardiac arrest. It has been proven to enhance the detection of reversible causes, assess compression quality during CPR, guide resuscitation efforts, and aid in determining survival prognosis based on specific findings.…”
Section: Discussionmentioning
confidence: 99%